Pengetahuan dan Kepatuhan Remaja Putri dalam Mengkonsumsi Tablet Tambah Darah di Desa Pariti Kecamatan Sulamu Kabupaten Kupang - Agatha F. Dora Kolo; Ananda Juventiny Radjah; Anastasia Intan Bani Wano; Anggreny R. Heda M. Banik; Matje Meriaty Huru; Namsyah Baso; Mariana Ngundju Awang; Agustina Abuk Seran; Melinda Rosita Wariyaka; Ni Luh Made Diah Putri Anggaraeningsih (Jurnal Medicare, 2025)
Anemia is one of the health problems that is still a serious concern in Indonesia, especially in adolescent girls. Adolescent girls are included in the high-risk group of suffering from anemia because they are in a period of rapid growth and begin to experience menstruation, so the need for iron increases. Iron deficiency anemia in adolescents not only has an impact on physical conditions such as fatigue and low immunity, but also has an impact on reducing study concentration, academic achievement, and reproductive health in the future. Adolescent girls who suffer from anemia are at risk of developing anemia during pregnancy and have an impact on the growth and development of the fetus in the womb and have the potential to give birth to babies with stunting or low birth weight (BBLR). This study aims to find out the knowledge about anemia and compliance in consuming blood supplement tablets in adolescent girls in Pariti Village, Sulamu District, Kupang Regency. This study uses a descriptive design with a Cross Sectional approach. The population in this study is 35 adolescent girls with Purposive Sampling technique. Data analysis uses univariate frequency distribution. The results showed that most of the young women had good knowledge of anemia while most of the young women had a low level of adherence in consuming blood-boosting tablets.